The relative information content of audited and unaudited financial data releases - R. F. Knight; J. F. Affleck-Graves (South African Journal of Business Management, 1987)
This article reports the results of a study which empirically investigates the relative information content of the three statutory reports required in terms of the Companies Act (1973) (viz. the interim report, the preliminary report and the annual report) in the context of the Johannesburg Stock Exchange. The relative information content of audited and unaudited data releases was likewise evaluated in this setting. The results presented indicate that the three statutory reports referred to each have significant information content although the PR appears to have a significantly larger information content than the others. Surprisingly, audited data do not appear to have a significantly different information content than unaudited data. A possible explanation which is tentatively offered is that audited data releases tend to be far less timely than unaudited data releases and this feature may result in a decaying of the former's incremental information content, if indeed any exists.
Keywords: 650